2021
DOI: 10.1002/ente.202100928
|View full text |Cite
|
Sign up to set email alerts
|

Proton Radiation Hardness of Perovskite Solar Cells Utilizing a Mesoporous Carbon Electrode

Abstract: When designing spacefaring vehicles and orbital instrumentation, the onboard systems such as microelectronics and solar cells require shielding to protect them from degradation brought on by collisions with high‐energy particles. Perovskite solar cells (PSCs) have been shown to be much more radiation stable than Si and GaAs devices, while also providing the ability to be fabricated on flexible substrates. However, even PSCs have their limits, with higher fluences being a cause of degradation. Herein, a novel s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Organometal halide perovskite solar cells (PSCs) are becoming promising for space applications. [4][5][6] Compared to solar cells based on group III-V materials for space applications, perovskite have a lower manufacturing cost [7][8][9][10] and comparable [11][12][13][14][15][16][17][18][19][20][21][22][23][24] or even better [25,26] radiation tolerance. In addition, bandgaps of perovskites are tunable making them suitable for multijunction tandems with high power conversion efficiencies (PCEs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organometal halide perovskite solar cells (PSCs) are becoming promising for space applications. [4][5][6] Compared to solar cells based on group III-V materials for space applications, perovskite have a lower manufacturing cost [7][8][9][10] and comparable [11][12][13][14][15][16][17][18][19][20][21][22][23][24] or even better [25,26] radiation tolerance. In addition, bandgaps of perovskites are tunable making them suitable for multijunction tandems with high power conversion efficiencies (PCEs).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that PSC with carbon rear electrode can withstand 150 keV proton irradiation with accumulated fluence of 10 15 photons cm −2 with minimum (<0.07%) PCE loss. [24] This is outstanding as the proton irradiation fluence is equivalent to ≈1000 years of irradiation on the low earth orbits (LEOs).…”
Section: Introductionmentioning
confidence: 99%
“…S6, ESI†). 42 At low wavenumbers, intermediate phase II (green) showed Raman peaks identical to those of intermediate phase I, and at high wavenumbers, there was no increase in the Raman signal. On the other hand, the Raman mapping image of the CHAI-antisolvent-bathed sample exhibited three different phases, including intermediate phase I (orange).…”
Section: Resultsmentioning
confidence: 98%
“…As shown in Figure 5, they found that PSCs based on TFMS 30 second-doped CNT obtained a champion PCE of 17.56%, with enhanced stability. Other carbon materials have been reported, such as mesoporous carbon [219], carbon nanofiber [220], graphite [221], and graphene [222].…”
Section: Electrodementioning
confidence: 99%